THE IMPLEMENTATION OF THE GAME-BASED LEARNING METHOD THROUGH ONLINE EDUCATIONAL GAMES USING KAHOOT TO IMPROVE ENGLISH VOCABULARY MASTERY OF GRADE I STUDENTS AT GLR CHRISTIAN ELEMENTARY SCHOOL SURABAYA - Febe Eka Widarma; Adrie Frans Assa; Dwi Murwani W. Pramono; Sarah Prasasti (Adisam Publisher, 2026)
This study explored the effectiveness of Game-Based Learning (GBL) using Kahoot to enhance English vocabulary mastery among Grade I-B students at GLR Christian Elementary School. Conducted through Classroom Action Research (CAR) over three cycles, the method showed consistent improvement in student performance. Average scores rose from 88.59% (pre-test) to 98.85% (Cycle I), dipped slightly to 97.95% (Cycle II), and increased to 99.10% (Cycle III). Standard deviation dropped significantly, indicating more consistent achievement. The GBL approach also improved student engagement, independence, confidence, and vocabulary retention. All students achieved the learning standard. These results support previous research on the benefits of GBL in enhancing motivation and language skills. Kahoot is recommended as an effective and engaging tool for vocabulary instruction.